Storytelling for personal connection: A pedagogical strategy to localise fashion education - Carla Roos; Neshane Harvey (University of Johannesburg, 2024)
The 2015 student protests, #RhodesMustFall and #FeesMustFall, gave rise to the call to decolonise curricula and end the dominance of Western ideologies in South African higher education (HE). The argument put forward in this paper is the need to shift from a traditional approach to a humanised pedagogical approach, wherein students frame knowledge around individual experiences to construct personal and shared understanding. Although limited scholarship around decolonising South African fashion HE exists, such scholarship does not focus on storytelling and circle learning as pedagogical strategies. To address this research gap, narrative humanism, referred to in this research as storytelling, and circle learning are put forward as pedagogical strategies to integrate student identities for personal connection in South African fashion HE. This paper aims to explore the affordances of storytelling and circle learning to decolonise South African fashion HE. Through qualitative action research, two teaching and learning interventions, termed the pilot and main studies, were designed and applied with fashion students at a South African HE institution. Data collection entailed semi-structured student questionnaires, artefacts, and a reflective research journal. To analyse the data, content analysis was employed. The findings reveal that, irrespective of cultural lived experiences or diverse backgrounds, storytelling afforded a decolonised approach in terms of inclusivity, collaboration, and a safe environment for socially engaged dialogue and peer feedback. Similarly, circle learning seemed to reduce teacher-student power relations and contrasted traditional modes of delivery.  Circle learning appeared to encourage meaningful, engaged participation, affording a progressive pedagogical strategy to accommodate student and teacher voices in open dialogue. This paper contributes to the scholarship of teaching and learning in that storytelling and circle learning are suitable pedagogies to decolonise fashion education in the Global South.